Inovasi Desain Produk sebagai Strategi Meningkatkan Profitabilitas UMKM Kerajinan Rumahan - Maryam, Maryam; Intan Amalia, Cut; Hanum, Filia; Hamdiah, Cut; Wahyuna, Misra (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The enhancement of competitiveness and profitability of home-based craft MSMEs can be achieved through the implementation of product design innovation as a key strategy. This study employs a literature review approach aimed at examining the impact of innovative design on business performance and identifying the challenges and readiness of MSMEs in adopting such innovations. A qualitative approach was employed, entailing observations and interviews with MSME actors who have implemented design innovation. The findings indicate that product designs that align with market trends, ergonomics, and production efficiency can enhance turnover by up to 50% and expand market segmentation. However, challenges persist, including a paucity of design expertise, constrained access to capital, and suboptimal technological literacy. The strategic recommendations put forth include the enhancement of collaborative efforts among MSMEs, designers, and research institutions, in addition to the provision of training and government incentives. In summary, design is not merely an aesthetic matter; rather, it is a strategic investment that propels MSMEs toward sustainable, value-based growth.